A Scoping Review of Emergency Department Discharge Instructions for Children and Adolescents With Mental Disorders. Issue 10 (October 2018) - Murphy, Andrea L.; Curran, Janet; Newton, Amanda S.; Emberly, Debbie; McRae, Cecilia; MacPhee, Shannon
Abstract : Background: Although most young people under the age of 25 years with mental health presentations to the emergency department (ED) are discharged home, several studies suggest discharge instructions are inadequate. We conducted a scoping review to characterize and map the literature, identify research gaps, and prioritize targeted areas for future reviews for ED discharge instructions for young people with mental disorders. Methods: Our review was conducted in an iterative approach with 6 stages including identifying the research question, identifying relevant studies, study selection, data extraction, collaring and summarizing, and stakeholder engagement. We characterized the available information on discharge instruction interventions using the Behavior Change Wheel. Results: Of the 805 potential publications screened, 25 were included for extraction. Nine of the 25 articles focused on suicide or self-harm, 6 were on mental health in general or mixed groups, and 9 focused on alcohol, tobacco, or substance use in general. Five studies included younger children (ie, less than 12 years) but ages ranged significantly among studies. Education and persuasion were intervention functions most commonly reported in publications (n = 13 and n = 12, respectively). From the policy categories, recommendations regarding service provision were most frequently made from four publications. Descriptions of theory were limited in publications. Conclusions: The available literature regarding discharge instructions in the ED for youth with mental disorders is focused on certain content areas (eg, self injurious behaviors, substance use) with more work required in chronic mental disorders that make up a significant proportion of ED visits. Research that extends beyond education and with theoretical underpinnings to explain how and why various interventions work would be useful for clinicians, policy-makers, and other researchers.